Penegakan Hukum Lingkungan Ditinjau dari Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup - M. Faisal Rahendra Lubis; Isti Qomahnur Ananda; Nurpadila Nurpadila; Putri Rahmi Harahap; Aulia Rahmah Batubara (Lembaga Pengembangan Kinerja Dosen, 2026)
Environmental law enforcement is one of the important instruments in maintaining environmental sustainability in the midst of increasing industrial activities and technological developments that have the potential to cause pollution and environmental damage. Increasingly complex environmental problems require effective law enforcement to protect people's rights to obtain a good and healthy environment. This study aims to determine the development of environmental law enforcement in Indonesia and analyze the application of administrative, civil, and criminal law enforcement based on Law Number 32 of 2009 concerning Environmental Protection and Management. The research method used is normative legal research with a legislative approach and a conceptual approach, which is analyzed qualitatively descriptively. The results of the study show that environmental law enforcement in Indonesia is carried out through three main instruments, namely administrative law, civil law, and criminal law. Administrative law enforcement focuses more on preventive efforts through supervision and the application of administrative sanctions, while civil law enforcement aims to provide compensation and environmental restoration due to pollution or environmental damage. Meanwhile, criminal law enforcement is applied to perpetrators of environmental crimes to provide a deterrent effect and prevent the recurrence of similar violations. The implications of this study show that the success of environmental law enforcement does not only depend on the existence of laws and regulations, but is also influenced by the quality of law enforcement officials, the effectiveness of supervision, and public awareness in protecting and preserving the environment.